Performance appraisal of interventions on rapeseed-mustard promoted through front line demonstrations under rainfed farming - Narinder Paul,; AS Charak,; RS Bandral,; Munish Sharma,; Amitesh Sharma, (Journal of Oilseed Brassica, 2026)
Present investigation was carried out to assess the performance and overall impact of technological interventionspromoted through Front Line Demonstrations (FLDs) on rapeseed mustard by Krishi Vigyan Kendra (KVK),SKUAST-J, Doda in rainfed areas of Doda District. In all, 149 farmers on whose fields FLDs were laid outon improved varieties of rapeseed mustard, recommended seed rate, application of recommended doses offertilizer and plant protection measures from rabi 2010-11 to rabi 2013-14 constituted the sample for thepresent investigation. Extension Gap (ExtGp), Technology Gap (TecGp) and Technology Index (TecInx)were calculated to assess the performance and overall impact of demonstrated technological interventions onrapeseed mustard. Technology Gap (TecGp) in the range of 431-499 Kg ha-1 for rapeseed and 380-640 Kgha-1 for mustard, Extension Gap (ExtGp) in the range of 194-254 Kg ha-1 for rapeseed and 107-215 Kg ha-1for mustard; and Technology Index (TecInx) in the range of 35.92-42.50 per cent for rapeseed and 31.67-53.33 per cent for mustard were found. The percent increase in the yield of rapeseed for the technologicalinterventions demonstrated through FLDs has been found to be in the range of 39.11 to 66.90 %. Similarly, incase of mustard crop, the per cent increase in yield has been found to be 23.62 to 42.82 % over the farmers’practice.